Waqf and trust: the nature, structures and socio-economic impacts. Issue 4 (8th July 2019) - Abdullah, Mohammad
Abstract : Purpose: This paper aims to compare and contrast the concept, mechanism and functions of the two socio-economic institutions, i.e. waqf (Islamic trust) and English trust. It endeavours to juxtapose the salient features of waqf and trust with an objective to examine the nature of similarities and dissimilarities between the two institutions. Design/methodology/approach: This paper applies the socio-legal research methodology and uses qualitative paradigm to analyse the literature. The paper is based on a desk-based research. Findings: This paper finds that there is nothing intrinsically rigid in the jurisprudential paradigm of waqf which might impinge upon either the efficiency or effectiveness of the waqf vis-à-vis trust. The main findings of the paper are encapsulated in underlining certain Shariah principles which essentially hold waqf from transforming into a trust-like secular institution. Research limitations/implications: This paper compares the jurisprudential underpinnings and conceptual frameworks of waqf and trust, and it does not evaluate their efficiency or effectiveness in empirical terms. The underlying socio-economic efficiency and impacts of the two institutions can be examined empirically in separate comparative case studies. Practical implications: This paper examines and critically analyses the different socio-economic implications that waqf and trust entail for the societies in which they function. This analysis is important for the policy recommendations towards protecting the religious identity of waqf while re-structuring its models. Originality/value: The main contribution of the paper is encapsulated in the critical analysis of how the paradigms of the two institutions, i.e. waqf and trust, which appear similar in form but differ in the substance, are shaped and governed.